Formulation of rizatriptan benzoate fast dissolving buccal fi lms by emulsion evaporation technique - Vidyadhara, Suryadevara; Sasidhar, Reddyvallam Lankapalli; Balakrishna, Thalamanchi; Vardhan, Malapolu Santha (International Journal of Pharmaceutical Investigation)
Aim: The present study deals with the formulation of fast dissolving fi lms of Rizatriptan benzoate that is used for the treatment of Migraine. The concept of fast-dissolving drug delivery emerged from the desire to provide patient with more conventional means of taking their medication. Materials and Methods: In the present research work, various trials were carried out using film forming agents such as maltodextrin, gum karaya and xanthan gum to prepare an ideal film. Emulsion evaporation method was used for the preparation of films. The prepared films were evaluated for weight uniformity, drug content, film thickness, folding endurance, dispersion test and curling. The in vitro dissolution studies were carried out using simulated salivary fluid (pH 6.8 phosphate buffer). Results: About 97% of the drug was found to be released from the film within 10 min that is a desirable character for fast absorption. The drug excipient interaction studies carried out by differential scanning calorimetry analysis and Fourier transform infrared studies revealed that there were no major interactions between the drugs and excipients used for the preparation of films. Conclusion: Fast dissolving films of Rizatriptan benzoate prepared by emulsion evaporation technique were found to be suitable for eliciting better therapeutic effect in the treatment of migraine.
Keywords: Emulsion evaporation method; fast dissolving fi lms; gum karaya; maltodextrin; rizatriptan benzoate; xanthan gum